2017
DOI: 10.1038/bjc.2017.238
|View full text |Cite
|
Sign up to set email alerts
|

Intracrine VEGF signalling mediates colorectal cancer cell migration and invasion

Abstract: Background:Vascular endothelial growth factor (VEGF) and its receptors (VEGFRs) are key regulators of angiogenesis, affecting endothelial cell survival and function. However, the effect of VEGF-VEGFR signalling on tumour cell function is not well understood. Our previous studies in colorectal cancer (CRC) cells have demonstrated an intracrine VEGF/VEGFR1 signalling mechanism that mediates CRC cell survival and chemo-sensitivity. Since extracellular VEGF signalling regulates migration of endothelial cells and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
58
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 42 publications
3
58
0
1
Order By: Relevance
“…VEGFA induces the migration of endothelial cells and lymphatic endothelium through activation of VEGFR2 (Suzuki et al 2008, Dellinger & Brekken 2011. Bhattacharya et al (2017) suggested that VEGF regulates colorectal cancer cell invasion and migration via intracrine VEGF signalling mediated by VEGFR1. Bhattacharya et al (2017) suggested that VEGF regulates colorectal cancer cell invasion and migration via intracrine VEGF signalling mediated by VEGFR1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…VEGFA induces the migration of endothelial cells and lymphatic endothelium through activation of VEGFR2 (Suzuki et al 2008, Dellinger & Brekken 2011. Bhattacharya et al (2017) suggested that VEGF regulates colorectal cancer cell invasion and migration via intracrine VEGF signalling mediated by VEGFR1. Bhattacharya et al (2017) suggested that VEGF regulates colorectal cancer cell invasion and migration via intracrine VEGF signalling mediated by VEGFR1.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, to eliminate the influence of gravity on transwell assay, hDPSCs was seeded on the back of chambers and VEGFA was placed in the upper chambers, and the results were consistent with those of conventional experiments (data not shown). Previous studies have revealed that VEGF regulates cell migration via several signalling pathways (Simons et al 2016, Bhattacharya et al 2017. VEGF promotes human MSC migration via an ERK MAPK-and FAK-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have implicated that VEGFR activation led to an increase in expression of the EMT-associated transcription factors Snail, Twist, and Slug which regulated the expression of epithelial markers E-cadherin to induce cell migration and invasion in cancer cells. [48][49][50] As the important roles of vascular endothelial growth factor VEGF and VEGFR in carcinogenesis, therapeutic strategies against these targets have been widely studied. 51,52 Gastric cancer is one of the indications for VEGF/VEGFR-targeted therapy based on the angiogenic evidence.…”
Section: Discussionmentioning
confidence: 99%